An Analysis of an AI-Integrated Student- Centered Promotional Video for Educational Institutions: A Qualitative Descriptive Study - Leni Rohliah; Sri Gustiani; Wirda Ningsih; Fransiska Amelia Tarigas; M. Ri’fat Fadhlurrahman; Harum Maulita (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
This study examines the creation and application of an institutional promotional video integrating student-centered scriptwriting and AI voice generation. This study aims to evaluate the effectiveness, strengths, and weaknesses of the outcome product from pedagogical and technological perspectives. The study uses a qualitative descriptive design to analyze the product along four dimensions based on four key aspects; content quality, narration, technical quality, and promotional effectiveness. The data were collected through documentation, reflective observation, and review of project records. Findings indicate that the integration of student-centered learning in script development encouraged creativity, collaboration, and ownership, while the use of AI voice technology enhanced cost efficiency and consistency in narration. However, limitations were detected in the emotional expressiveness of the AI- generated voice and the briefness of the video, which reduced narrative depth. The study suggests that integrating student‐centered methods using AI techniques can provide a pedagogically significant and technically interesting model for institutional promotion. Suggested recommendations include the use of hybrid forms, continuing students' participation in post-production, and carrying out studies of audience perception in future research.